Quantum mechanics - Goswami, Amit (Dubuge: Wm C Brown Pub., 1992)
Offers an introduction to quantum mechanics, covering current material on the solution of the Schroedinger equation in momentum representation; two-dimensional motion; EPR and Schroedinger cat paradoxes; linear potential to illustrate quark-quark interaction; and Bell inequality.
Includes bibliographical reference; ; Appendix 525-528p.; Bibliography 529-530.; Index 531-536p.
Keywords: Quantum mechanics; Physics